(untitled) (Revista de Estudos da Linguagem, 2015)
Abstract: The present study aimed to investigate how different Voice Onset Time (VOT) patterns are categorized by native speakers of American English and Brazilian Learners of English. American English and Brazilian Portuguese diverge as to the voicing pattern of plosive consonants, for the VOT cue plays different roles in the distinction between voiced and voiceless consonant categories in each system. This study contrasted four VOT patterns (Negative VOT, Zero VOT, Positive VOT and a manipulated pattern, named Artificial Zero VOT) in two perceptual tasks (AxB discrimination and identification tests), and verified how the two groups of participants categorized these patterns. Results reinforce the idea that speech perception is multimodal and, therefore, the action of multiple cues must be taken into account when we consider phonetic-phonological processes. Keywords: Voice Onset Time; Speech Perception; Discrimination; Identification. Resumo: O presente estudo buscou investigar como diferentes padrões de Voice Onset Time (VOT) são categorizados por falantes nativos de Inglês Americano e aprendizes brasileiros de Inglês. O Inglês Americano e o Português Brasileiro divergem quanto ao padrão de vozeamento das consoantes plosivas, uma vez que a pista VOT desempenha diferentes papéis na formação de categorias de consoantes vozeadas e desvozeadas em cada sistema. Este estudo contrastou quatro padrões de VOT (VOT Negativo, VOT Zero, VOT Positivo e um padrão manipulado, nomeado VOT Zero Artificial) em duas tarefas perceptuais (testes de discriminação AxB e identificação), e verificou como os dois grupos de participantes categorizaram esses padrões. Os resultados corroboram a ideia de que a percepção da fala é multimodal e, portanto, a ação de múltiplas pistas acústicas deve ser levada em consideração quando abordamos processos fonético-fonológicos. Palavras-chave: Voice Onset Time; Percepção da Fala; Discriminação; Identificação.